The experiences of race relations amongst student leaders at a historically white South African university - Selowa, Hlengiwe; Motileng, Benny (PINS-Psychology in Society, 2024)
Recent protest movements such as #Rhodesmustfall and #FeesMustFall have highlighted uneasy race relations at South African universities. Although such incidents are crucial, equally important are the everyday realities of race relations that continue to define student lives in these institutions. The purpose of this study was to provide an understanding of student leaders’ experiences of race relations at a historically white South African university. Guided by a qualitative research approach, Critical Race Theory (CRT) was the framework we used to explore race relations amongst student leaders. Purposive sampling was employed to recruit six student leaders across racial groups. They participated in a forty-five-minute semi-structured interview. Interpretive phenomenological analysis (IPA) was used to analyse the data. The findings suggest that the history and identities of universities as racially segregated in an unequal society, impacts race relations. Racial discrimination and distrust hamper racial integration in the student body and external political factors also affect student leaders’ experiences of race relations. Our findings do show that friendships present an important opportunity to foster positive race relations, even though friendships are largely class dependent. We recommend that universities invest in personnel diversity training and the creation of platforms for intercultural and interracial exchanges.